Nitrogen oxides and CO2 from an Oxisol cultivated with corn in succession to cover crops - Carvalho, Arminda Moreira de; Bustamante, Mercedes Maria da Cunha; Coser, Thais Rodrigues; Marchão, Robélio Leandro; Malaquias, Juaci Vitória (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of two legumes (Crotalaria juncea and Mucuna pruriens), as cover crops, and of natural fallow, as a control treatment, on the emissions of NOx, N2O, and CO2 from an Oxisol cultivated with corn, under conventional and no-tillage systems, in the Cerrado region, in Central Brazil. Variations of CO2 fluxes in the soil were explained mainly by soil humidity and, in the legumes, under conventional system, by soil NH4+-N concentration. Plots with legumes under no-tillage system had higher annual emissions of CO2, NOx, and N2O than natural fallow. Results show that the use of legumes as cover crops favors the emissions of NOx-N + N2O-N and CO2-C. However, when considering the potential for mitigation of CO2 and nitrogen oxide emissions from the soil, it is important to evaluate changes in soil carbon and nitrogen stocks.